SALESPERSON PERFORMANCE IN THE BANKING INDUSTRY: THE ROLE OF PRODUCT KNOWLEDGE, COMMUNICATION SKILLS, AND CUSTOMER VISIT - Kurniawan Panji; Suarmanayasa I Nengah; Heryanda Komang Krisna (SOSIOEDUKASI, 2026)
This research aims to analyze the influence of product knowledge, communication skills, and customer visits on salesperson performance at PT. Bank Rakyat Indonesia (Persero) Tbk., Singaraja Branch Office. The study employed a quantitative causal research design to examine the relationships between these variables. A census sampling technique was utilized, involving the entire population of 111 salespersons, which includes Relationship Managers and Mantri. Data were collected through structured questionnaires using a 5-point Likert scale and analyzed using multiple linear regression, partial t-tests, and simultaneous F-test. The results demonstrate that product knowledge, communication skills, and customer visits each have a positive and significant partial effect on salesperson performance. Simultaneously, these three variables significantly influence performance with an F-value of 40.816 (p < 0.05), accounting for 53.4% of the performance variance. The study indicates that while each factor is a critical determinant, their synergistic integration is essential for achieving optimal sales targets and volume growth. The study concludes that product knowledge, communication skills, and customer visits serve as vital predictors of salesperson success in the banking sector. These findings suggest that management should prioritize periodic product refreshment and structured monitoring of visit quality to maintain performance stability and competitive advantage.